2005
DOI: 10.2174/138955705774933383
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of HIV-1 Transcription by Cytokines and Chemokines

Abstract: Infection with HIV results in the modulation of circulating levels of many host factors. Several host proteins that are up-regulated in HIV infection have the potential to influence virus replication. More specifically, the transcription of HIV-1 can be modulated in vivo by host proteins, including cytokines and chemokines. Cytokines modulate transcription mediated by the HIV-1 long terminal repeat (LTR) via multiple signal transduction pathways with resulting recruitment of numerous transcription factors, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 113 publications
0
28
0
2
Order By: Relevance
“…The NGF enhancement of HIV-1 transcription was more powerful than the TNF-␣ stimulation, a classic HIV-1 LTR activator. 9 It has already been proposed that NGF could activate HIV-1 LTR 41,42 ; however, these previous works were performed using glial and neuronal cell lines transfected with HIV-LTR-CAT vectors. Therefore, our study included a more physiologic model of induction of HIV-1 transcription on NGF stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NGF enhancement of HIV-1 transcription was more powerful than the TNF-␣ stimulation, a classic HIV-1 LTR activator. 9 It has already been proposed that NGF could activate HIV-1 LTR 41,42 ; however, these previous works were performed using glial and neuronal cell lines transfected with HIV-LTR-CAT vectors. Therefore, our study included a more physiologic model of induction of HIV-1 transcription on NGF stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…6 In this context, cytokines and other endogenous soluble factors can modulate the viral replicative cycle, 7,8 and several studies support the influence of these molecules over both the course of the disease and HIV-1 biology. [7][8][9] Pro-inflammatory cytokines, such as tumor necrosis factor-␣ (TNF-␣) and interleukin-6 (IL-6), up-regulate HIV-1 replication, whereas others with anti-inflammatory properties, such as type 1 interferon (IFN), IL-10, and IL-27, may diminish viral replication. 8,10 It has been found that some cytokines interfere with HIV-1 replication by modulating cellular restriction factors to the virus.…”
Section: Introductionmentioning
confidence: 99%
“…The promoter is divided into four regions: the TAR element, the core promoter, the core enhancer, and the modulatory region, which contains a negative regulatory element (NRE) (25). A number of transcription factors induce HIV promoter activity, such as C/EBP, NF-〉, NFAT, AP-1, and Sp1 (7,13,19). Others are suppressors of HIV promoter activity, the most notable of which are YY-1, LSF, p50 homodimer, CBF-1, CTIP2, and c-myc (5,9,18,23,35,37).…”
mentioning
confidence: 99%
“…Owing to the tightly coupled regulation of the HIV long terminal repeat (LTR) by many T cell regulatory signals and the dependence of productive HIV replication on the activation state of the host cell, we hypothesized that minocycline treatment would decrease HIV replication by decreasing the activation state of the host cell [10][11][12]. In this study, we demonstrate that minocycline decreases single-cycle HIV replication, intracellular viral RNA levels after in vitro infection of primary human CD4 + T cells, reactivation of HIV from a primary CD4 + T cell-derived model of HIV latency, and reactivation of HIV from resting CD4 + T cell reservoirs from patients who have clinically undetectable viremia during HAART.…”
mentioning
confidence: 99%